Correction to: Climate‐driven insect pest outbreaks and food security risks: a review of adaptive strategies for resilient agriculture - Kamran Haider; Dilawar Abbas; Farman Ullah; Muhammad Ijaz; Muhammad Ikram; Kamil Kabir; Khalid Ali Khan; Jose Galian (Journal of Pest Science, 2026)

Integrative mechanisms of photoperiod and temperature regulation in insect diapause - Dilawar Abbas; Kamran Haider; Farman Ullah; Muhammad Yasir Ali; Umer Liaqat; Maolin Hou (Journal of Pest Science, 2026)

Climate-driven insect pest outbreaks and food security risks: a review of adaptive strategies for resilient agriculture - Kamran Haider; Dilawar Abbas; Farman Ullah; Muhammad Ijaz; Muhammad Ikram; Kamil Kabir; Khalid Ali Khan; Jose Galian (Journal of Pest Science, 2026)

Miexianling: a novel dual-action pesticide for sustainable pine wilt disease management through integrated beetle and nematode control - Min Li; Guanyi Cheng; Ming Xu; Mengyao Wang; Yue Li; Jingeng Tang; Yinchu Chai; Kangquan Chen; Muhammad Faizan Latif; Ying Pei; Ting Yang; Yajing Song; et al. (Journal of Pest Science, 2026)

Insect resilience: unraveling responses and adaptations to cold temperatures - Farman Ullah; Arzlan Abbas; Hina Gul; Ali Güncan; Muhammad Hafeez; Basana-Gowda Gadratagi; Lizette Cicero; Ricardo Ramirez-Romero; Nicolas Desneux; Zhihong Li (Journal of Pest Science, 2024)

Ecotoxicological risk assessment of combined insecticidal and thermal stresses on Trichogramma chilonis - Muhammad Ahmad; Muhammad Kamran; Muhammad Nabeel Abbas; Sarfraz Ali Shad (Journal of Pest Science, 2024)

Current knowledge and implementations of Bemisia tabaci genomic technologies for sustainable control - Muhammad Arslan Mahmood; Rubab Zahra Naqvi; Hamid Anees Siddiqui; Imran Amin; Shahid Mansoor (Journal of Pest Science, 2023)

Supercooling capacity and cold tolerance of the South American tomato pinworm, Tuta absoluta, a newly invaded pest in China - Xiao-wei Li; Dong Li; Zhi-jun Zhang; Jun Huang; Jin-ming Zhang; Muhammad Hafeez; Li-kun Wang; Wen-chao Guo; Yao-bin Lu (Journal of Pest Science, 2021)
Tuta absoluta is a devastating invasive pest worldwide, causing severe damage to the global tomato industry. It has been recorded recently in the northwestern border areas of China, posing a significant threat to tomato production. It was presumed that the region's winter-related low temperatures would avert the alien species from successfully overwintering. In this study, the supercooling capacity and low-temperature tolerance of this pest were examined under laboratory conditions and its overwintering potential in Xinjiang was estimated. The results showed that the lowest supercooling point was recorded in the adult stage (− 19.47 °C), while the highest (− 18.11 °C) was recorded in the pupal stage. The supercooling points of pupae and adults were not influenced by gender. The Ltemp 50 and Ltemp 90 of female and male adults were the lowest when exposed to cold for 2 h. However, when the duration of exposure extended from 4 to 10 h, the Ltemp 50 and Ltemp 90 of female and male pupae were the lowest. Comparison of the lowest Ltemp 50 and Ltemp 90 with temperatures in January indicated that T. absoluta might not be able to overwinter in most of the northern and central regions of Xinjiang. However, in the southern regions, the extremely low temperature was higher than the Ltemp 90 , suggesting that T. absoluta has a higher overwintering potential in these regions. These results form a basis for predicting the dispersal potential and possible geographic range of this pest in Xinjiang. In addition, our findings provide guidance for the control of this pest by reducing overwintering shelters.

Correction to: Fluctuating temperatures influence the susceptibility of pest insects to biological control agents - Muhammad Usman Ghazanfar; Steffen Hagenbucher; Jörg Romeis; Giselher Grabenweger; Michael Meissle (Journal of Pest Science, 2020)

Downregulation of chitin synthase A gene by diallyl trisulfide, an active substance from garlic essential oil, inhibits oviposition and alters the morphology of adult Sitotroga cerealella - Sakhawat Shah; Muhammad Hafeez; Meng-Ya Wu; Su-Su Zhang; Muhammad Ilyas; Gang Wu; Feng-Lian Yang (Journal of Pest Science, 2020)

Fluctuating temperatures influence the susceptibility of pest insects to biological control agents - Muhammad Usman Ghazanfar; Steffen Hagenbucher; Jörg Romeis; Giselher Grabenweger; Michael Meissle (Journal of Pest Science, 2020)

Loop-mediated isothermal amplification for the detection of R81T mutation in nAChR with crude genomic DNA extracted from individual Myzus persicae - Muhammad Umair Sial; Zhenzhen Zhao; Lan Zhang; Yanning Zhang; Liangang Mao; Hongyun Jiang (Journal of Pest Science, 2020)

The importance of alternative host plants as reservoirs of the cotton leaf hopper, Amrasca devastans, and its natural enemies - Rabia Saeed; Muhammad Razaq; Ian C. W. Hardy (Journal of Pest Science, 2015)

Residual efficacy of thiamethoxam, Beauveria bassiana (Balsamo) Vuillemin, and diatomaceous earth formulation against Rhyzopertha dominica F. (Coleoptera: Bostrychidae) - Waqas Wakil; Tahira Riasat; Muhammad Ashfaq (Journal of Pest Science, 2012)

Field evolved resistance to carbamates, organophosphates, pyrethroids, and new chemistry insecticides in Spodoptera litura Fab. (Lepidoptera: Noctuidae) - Sarfraz Ali Shad; Ali H. Sayyed; Sahar Fazal; Mushtaq A. Saleem; Syed Muhammad Zaka; Muhammad Ali (Journal of Pest Science, 2012)

Comparison of biological parameters between the invasive B biotype and a new defined Cv biotype of Bemisia tabaci (Hemiptera: Aleyradidae) in China - Bao-Li Qiu; Fang Dang; Shao-Jian Li; Muhammad Z. Ahmed; Feng-Liang Jin; Shun-Xiang Ren; Andrew G. S. Cuthbertson (Journal of Pest Science, 2011)

Preference and performance of Plutella xylostella (L.) (Lepidoptera: Plutellidae) on canola cultivars - Seyed Ali Asghar Fathi; Maryam Bozorg-Amirkalaee; Rana Muhammad Sarfaraz (Journal of Pest Science, 2011)

Dynamics of resistance to organophosphate and carbamate insecticides in the cotton whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) from Pakistan - Mushtaq Ahmad; M. Iqbal Arif; Muhammad Naveed (Journal of Pest Science, 2010)

Phylogenetic analysis of Bemisia tabaci (Hemiptera: Aleyrodidae) populations from cotton plants in Pakistan, China, and Egypt - Muhammad Z. Ahmed; Shun-Xiang Ren; Nasser S. Mandour; M. N. Maruthi; Muhammad Naveed; Bao-Li Qiu (Journal of Pest Science, 2010)

Biological impact of harmaline, ricinine and their combined effects with Bacillus thuringiensis on Spodoptera exigua (Lepidoptera: Noctuidae) - Muhammad Rizwan-ul-Haq; Qiong Bo Hu; Mei Ying Hu; Qing Shen Lin; Wan Li Zhang (Journal of Pest Science, 2009)

Predatory potential of three hunting spiders inhabiting the rice ecosystems - Hafiz Muhammad Tahir; Abida Butt (Journal of Pest Science, 2009)

Contribution of cultivated crops, vegetables, weeds and ornamental plants in harboring of Bemisia tabaci (Homoptera: Aleyrodidae) and associated parasitoids (Hymenoptera: Aphelinidae) in cotton agroecosystem in Pakistan - Muhammad Naveed; Abdus Salam; Mushtaq Ahmad Saleem (Journal of Pest Science, 2007)